2015
DOI: 10.1039/c5cc03425f
|View full text |Cite
|
Sign up to set email alerts
|

Dimeric platinum–stannylene complexes by twofold ligand transfer from an NHC adduct to an organotin(ii) hydride

Abstract: Upon ligand transfer of hydrides and NHC a dimeric formal Pt(I)–Sn(I) (2) complex was obtained from a 1:1 reaction of Pt(cod)2 (cod = 1,5-cyclooctadiene) and the NHC adduct to a bulky terphenyltin(II) hydride Ar*SnH(NHC) (1) [NHC = 1,3,4,5-tetramethylimidazol-2-ylidene, Ar* = 2,6-(2,4,6-triisopropylphenyl)C6H3]. The bridging stannylene Sn atoms each reveal an individual coordinative interaction with the platinum atoms and the hydrides with ‘non-classic’ Pt–H–Sn bonds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 51 publications
2
33
0
Order By: Relevance
“…[D 8 ]THF was distilled from LiAlD 4 and stored in a dry box. Terphenyl‐ iodide (Ar*I) ‐lithium derivative (Ar*Li(OEt 2 )),‐Sn II chloride (Ar*SnCl, Ar*GeCl), were prepared according to modified literature procedures and Sn IV trichloride (Ar*SnCl 3 ), Sn IV hydride, deuteride were prepared as previously described ,. (Ar*GeCl 3 ) was prepared according to a modified literature procedure .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[D 8 ]THF was distilled from LiAlD 4 and stored in a dry box. Terphenyl‐ iodide (Ar*I) ‐lithium derivative (Ar*Li(OEt 2 )),‐Sn II chloride (Ar*SnCl, Ar*GeCl), were prepared according to modified literature procedures and Sn IV trichloride (Ar*SnCl 3 ), Sn IV hydride, deuteride were prepared as previously described ,. (Ar*GeCl 3 ) was prepared according to a modified literature procedure .…”
Section: Methodsmentioning
confidence: 99%
“…Chemical shifts are reported in d values in ppm relative to external TMS ( 1 H, 13 C) and SnMe 4 ( 119 Sn) referenced in most cases on the residual proton signal of the solvent C 6 D 6 ( 1 H7 .15 ppm; 13 C1 28.0 ppm). 19 Fa nd 119 Sn-as well as 1 H and 13 C-spectra in [D 8 ]toluene, chlorobenzene-d 5 and 1,2-dichlorobenzene-d 4 were referenced using the chemical shift of the solvent 2 Hr esonance frequency and X = 25.145020 %f or 13 C, X = 37.290632 %f or 119 Sn, X = 40.480742 %f or 31 Pa nd X = 94.094011% for 19 F. [33] The proton and carbon signals were assigned where possible via ad etailed analysis of 1 H, 13 C{ 1 H} or 13 C{ 1 H}-UDEFT, 1 H-1 H COSY, 1 H-13 CH SQC, 1 H-13 CH MBC NMR spectra. Selected 1D-NMR spectra of the compounds and mixtures can be found in the Supporting Information.…”
Section: Nmr Spectroscopymentioning
confidence: 99%
“…[6] We also reported the successful stoichiometric abstraction of H 2 from bulky substituted Ar*SnH 3 (Ar* = 2,6-(trip) 2 phenyl, trip = 2,4,6-triisopropylphenyl) with two equivalents of simple N-heterocyclic carbenes (NHCs) to yield the NHC adducts of Ar*SnHi na lmost quantitative yields. [13] We now wish to report on the variety of products observed in the stoichiometric dehydrogenation of Ar'SnH 3 with simple N-heterocyclic carbenes of slightly increasing stericb ulk. In the course of our studies on the reactivity of TripSnH 3 and Ar*SnH 3 we found that the derivatives of the relatively small Trip moiety are thermally labile and prone to decompositiony ielding mixtures that circumventt horough identification and characterisation of the products.…”
Section: Introductionmentioning
confidence: 99%
“…reported the reaction of an osmium benzyl complex with organotin trihydride tripSnH 3 (trip=2,4,6‐triisopropylphenyl) to give an organohydridostannylene complex upon toluene elimination . By reacting an NHC adduct of a low valent tin hydride [Ar*SnH( Me NHC)] with the platinum complex [Pt(cod) 2 ] a dimeric tin–platinum complex featuring bridging hydride ligands was characterized at low temperature . We have been exploring the chemistry of organotin and organogermanium trihydrides: Both, reductive elimination of hydrogen in reaction with various Lewis bases, as well as hydride abstraction to give highly reactive dihydridocations were studied .…”
Section: Introductionmentioning
confidence: 99%